Books: Outliers: The story of success - Cortés, Catalina (Base Diseño e Innovación, 2016)
Outliers, by Malcolm Gladwell is a book about the meaning of work and a journey through his own story and research about success. Many of us travel through life and work with the desire of being successful. This word can mean very different things depending on the context, story and aspirations of each in-dividual. Gladwell defines three aspects that need to occur in order to have a satisfying and meaningful work experience. These are autonomy, complexity and a connection be-tween effort and reward.